Analisis Faktor-Faktor Yang Dapat Mempengaruhi Inovasi Umkm Dalam Meningkatkan Daya Saing Produk Lokal - Vera Maria; Linda Nurkhalida; S. Ulfa. AB. AL (Master Manajemen, 2024)
The era of globalization is an era of competition, where all MSMEs (Micro, Small and Medium Enterprises) compete with each other in order to survive and develop their businesses to a better one. The purpose of this study is to analyze the factors that enable MSME innovation to increase the competitiveness of its products. The research method used is a descriptive method with a qualitative approach. Data are obtained through the results of literature studies. The results showed that there are two factors that greatly influence MSME innovation in increasing their competitiveness, namely internal factors (human resources, finance, management, and technology) and external factors (market, competition, and government policies). This research provides recommendations to be able to increase competitiveness to innovate in its products, namely by developing new or improved products, improving production processes, developing new marketing strategies and building strong brands